PENGARUH MOTIVASI BELAJAR DAN DISIPLIN TERHADAP PRESTASI BELAJAR SISWA DI SMA NEGERI 9 KOTA JAMBI - Muhammad Ardhi Bayu Pratama; Benar Sembiring (SJEE (Scientific Journals of Economic Education), 2023)
This study aims to find out is there any influence of learning motivation and learning discipline on student achievement in class XI SMA Negeri 9 Jambi City. The variables in this study consisted of learning motivation and learning discipline as independent variables and learning achievement as the dependent variable. Methods of data collection using questionnaires and documentation. Data analysis using percentage descriptive analysis and multiple regression analysis. The results showed that simultaneously learning motivation and learning discipline on student achievement in class XI students in class XI IPS at SMA Negeri 9 Jambi City, namely 21.9%, learning discipline has an effect on student achievement in class XI students in class XI IPS at SMA Negeri 9 Jambi City by 28.4 %. Simultaneously learning motivation and learning discipline on student achievement in class XI students in class XI IPS SMA Negeri 9 Jambi City with an effect of 41.5%, the remaining 58.5% of learning achievement XI IPS SMA Negeri 9 Jambi City is influenced by other factors that are not studied in this study. Keywords : Learning Motivation, Discipline, Learning Achievement